Security imperatives and societal implications for government: Perspectives in Nigeria - Princewill Onofere OKEREKA; Vincent Eseoghene EFEBEH; Lucas Nduka OLUKA (International Journal of Psychosocial Rehabilitation, 2020)
In the first half of the year 2020, Nigeria had recorded intensified violence spawn from the insurgent groups in the form of Boko Haram Islamic sect, Islamic State in West African Province (ISWAP), banditry and the self-styled Fulani herdsmen attacks in the North East, North West, and now in other regions of the country. These seemingly intensified and determined campaign of violence by these insurgent groups, and the ineptitudes of the Security Chiefs to contain the activities of these terrorists groups and criminal gangs, as well as the occasional violations of human rights and abuse of the rule of law, inarguably, resulted to the regular outcries for the protection of lives and properties, as well as the removal of the Security Service Chiefs in the country. This study, therefore, seeks to unveil the reasons behind the activities of these insurgent groups and the consequences of their actions to socio-economic development of the country. Also of pertinence is the need to x-ray the trends in attacks by the insurgents and criminal gangs. To achieve the objectives of this study, historical research design which is qualitative and explorative in nature was adopted. This means that data used were derived mainly from secondary source such as textbooks, journal publications, official documents, internet materials, among others. The study adopts Expectancy theory to examine the need for the government and security agencies to ensure the citizens are protected, and not particularly, the regime. Policy options were proffered to ameliorate the consequences of the activities of the insurgent groups and to strengthen the security agencies, especially the armed forces to enable them combat these insurgencies in the country. Moreover, the government needs to improve on border security to stem the inflow of jihadist groups, small and light weapons through the country’s porous borders with its neighbouring countries; and also on the forestry department in order to check the movement of these criminal groups who find our forests as safe for camping and training of their recruited members, among others.